Strategy Planning for Rice Seed Producer’s Information System Using Anita Cassidy Method - Jaja, Jaja; Purwanti, Santi; Herlawati, Herlawati (LPPM Universitas Islam 45 Bekasi, 2020)
Strategic planning of information systems on seed producers is an action that needs to be taken in order to maintain and make the business grow faster. However, such information system usually been created through the system development life cycle (SDLC) or other methods that appropriate for business. This study used Anita Cassidy method for strategic planning of rice seed producer’s information systems in XYZ Ltd., as case study. The following stages has been done, i.e. visioning, analysis, direction, and recommendations. The final results of the stages carried out recommend business applications that can be implemented, namely: Rice seed certification information systems, E-Commerce of Rice Seeds, Rice Type Determination Applications, Irrigation Control Applications, Paddy Pest Resolution Applications, Rice Growth Monitoring Applications, Personnel Information Systems, Payroll Information System, Procurement Information System, Financial Information System. Keywords: Information Systems, Information Systems Strategic Planning, Anita Cassidy Method